The problem of foreign borrowings in German scientific-and-technical terminology - A. M. Klyoster; M. S. Shumaylova (Омский научный вестник: Серия "Общество. История. Современность")
The paper presents the study of foreign borrowings in scientific and technical terminology, which are, on the one hand, influenced by the German language, by graphical, grammatical and lexical assimilation; on the other hand, themselves have an impact on the adoptive language. The authors consider the most common derivational types of borrowed terms. The paper emphasizes that the process of assimilation of Anglo-Americanisms is gradual and inconsistent. A distinctive feature of their functioning in the German scientific and technical terminology is their widespread use despite the incompleteness of their spelling and grammatical assimilation